The Resort Belokurikha – the Architectonics of Place and Trends of Territorial Planning - Pomorov, Sergey (project baikal, 2019)
The article presents the history of the formation and development of the resort «Belokurikha» and its current state with the emphasis on evaluation of the features of the architectonics of the place. The article describes the trends of territorial planning associated with the further development of the resort, which has high quality mountain recreational landscapes, attractive properties of natural landscapes, polystyle architecture and the identical cultural code inherent in this place.
Keywords: resort; resort area; place architectonics; architectural environment; territorial planning